Corporate governance and bank risk-taking: transitional economic evidence - Dat Nguyen (Journal of Applied Economics)
This study examines the impact of corporate governance on risk-taking in Vietnamese banks. Using data from 2007 to 2020 and employing the two-step generalized method of moments (GMM) technique, the study finds that certain aspects of corporate governance significantly influence bank stability efficiency. Specifically, the presence of female board members, independent directors, and larger board sizes are associated with improved stability efficiency, while the presence of foreign board members has a negative impact. These findings are consistent with agency theory, stewardship theory, and resource dependence theory. By employing the stochastic frontier approach, this research contributes to understanding how corporate governance characteristics can help mitigate risk-taking in emerging market contexts.